Application of collaborative serious gaming for the elicitation of expert knowledge and towards creating Situation Awareness in the field of infrastructure resilience. (January 2022) - Wehrle, Rebecca; Wiens, Marcus; Schultmann, Frank
Abstract: Increasing ageing of transport infrastructures requires a systematic resilience-based maintenance strategy. However, the assessment of risk and resilience is problematic due to the manifold influencing factors and mechanisms within the complex socio-technical system of infrastructure maintenance. This paper provides an analysis of the intricate processes and interdependencies, which influence the potential for resilient infrastructure maintenance. The presented iterative framework incorporates the elicitation of expert knowledge and a serious gaming application. Providing a valid environment for a systematic and guided dialogue among decision makers, serious gaming is highlighted as a valuable research tool that can effectively increase stakeholders' Situation Awareness and thus improve infrastructure resilience itself and its assessment. The authors developed a collaborative board game which emulates real-life decisions of stakeholders in the context of German waterways. In particular, the interaction of the players who take specific stakeholder roles contribute to a deeper understanding of the system, including the impacts of the players' decisions in the real-world system. The paper shows the contribution and potential of serious gaming, including a proposed integration into a Bayesian network as resilience assessment tool. It becomes obvious that the exploitation of expert knowledge to the end of improved systemic decision making requires that the application is closely aligned with the real-world system and the research method in all phases of gamification. On overall, the insights of this study suggest that serious collaborative gaming should be considered more in both research and practice, thus creating Situation Awareness among stakeholders of critical infrastructures (CI).